Easy sew jelly roll bags - Anderson, Jody (American Quilter's Society, 2013)
"Charming bags and totes designed exclusively to be made with 2 1/2 inch strips. If you can sew a seam, you can sew a bag or tote that is totally unique to you! Add beads, buttons, and trims to make a personal fashion statement. Full-size templates and all the directions you need"-- Provided by publisher.